Unified Algebras and Modules - Mosses, Peter D. (DAIMI Report Series, 1988)
This paper concerns the algebraic specification of abstract data types. It introduces and motivates the recently-developed framework of unified algebras, and provides a practical notation for their modular specification. It also compares unified algebras with the well known framework of order-sorted algebras, with underlies of OBJ specification language.